DIAPHYSEAL NUTRIENT FORAMINA IN DRIED HUMAN ADULT LONG BONES OF UPPER AND LOWER LIMBS IN PAKISTAN - Ullah, Najeeb (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Background: The circulation of blood in the bones is necessary for osteogenesis, maintenance of bone vitality, bone growth and repair of fracture and other injuries. The nutrient foramina are holes that allow blood vessels to pass through the bone cortex. Methodology: This was a cross-sectional study conducted from February 2013- Sep-tember 2013, at the department of Anatomy, Ayub Medical College (Osteology Sec-tion), Abbottabad and Department of Anatomy, Khyber Medical College (Osteology Section), Peshawar with the due consents of the heads of the institutions. The aim of the present study was to observe the diaphyseal nutrient foramina in the human upper and lower limb long bones. This study was done on 180 human long bones, consisting of humerii, radii, ulnae of upper limb and femora, tibiae and fibulae of lower limb bones with 30 bones each.. Results: Our study was conducted on 180 long bones of upper and lower limbs. More than 80% of the long bones of upper and lower limbs had single nutrient foramen, whereas occurrence of double nutrient foramina was around 18%. Direction of nutrient foramina in case of humerus was distal, where as in cases of radius and ulna direction was proximal. In case of femur direction of nutrient foramina was proximal where as in cases of tibia and fibula most of nutrient foramina were directed distally. Conclusion: The present study has provided additional information on the morphology, foramina index and topography of the nutrient foramina in the upper and lower limb long bones. The anatomical data is important to the clinicians as the micro-vascular bone transfer is becoming popular.